Redox enterprise: to ensure total satisfaction for our user / Sapphire Moujing... [et.al] - Moujing, Sapphire; Mazalan, Maisarah Syafiqah; Lukman, Rohaini Ainun; Motiyus, Aivenny Stacey; Ngah, Noor Zawani (2017)
Redox Enterprise is a partnership company aimed to provide the customers with high quality services producing biodegradable stain removal.